Small duct primary sclerosing cholangitis without inflammatory bowel disease is genetically different from large duct disease. (7th March 2014) - Næss, Sigrid; Björnsson, Einar; Anmarkrud, Jarl A.; Mamari, Said Al; Juran, Brian D.; Lazaridis, Konstantinos N.; Chapman, Roger; Bergquist, Annika; Melum, Espen; Marsh, Steven G. E.; Schrumpf, Erik; Lie, Benedicte A.; et al.
Abstract Background & Aims Small duct primary sclerosing cholangitis (PSC) is phenotypically a mild version of large duct PSC, but it is unknown whether these phenotypes share aetiology. We aimed to characterize their relationship by investigating genetic associations in the human leucocyte antigen (HLA) complex, which represent the strongest genetic risk factors in large duct PSC. Methods Four classical HLA loci (HLA‐A, HLA‐B, HLA‐C and HLA‐DRB1) were genotyped in 87 small duct PSC patients, 485 large duct PSC patients and 1117 controls across three geographical regions. Results HLA‐DRB1*13:01 (OR = 2.0, 95% CI 1.2–3.4, P = 0.01) and HLA‐B*08 (OR = 1.6, 95% CI 1.1–2.4, P = 0.02) were significantly associated with small duct PSC compared with healthy controls. Based on the observed frequency of HLA‐B*08 in small duct PSC, the strongest risk factor in large duct PSC, an estimated 32% (95% CI 4–65%) of this population can be hypothesized to represent early stages or mild variants of large duct PSC. This subgroup may be constituted by small duct PSC patients with inflammatory bowel disease (IBD), which greatly resembled large duct PSC in its HLA association. In contrast, small duct PSC without IBD was only associated with HLA‐DRB1*13:01(P = 0.03) and was otherwise distinctly dissimilar from large duct PSC. Conclusions Small duct PSC with IBD resembles large duct PSC in its HLA association and may represent early stages or mild variants of large duct disease. Different HLA associations in small duct PSC without IBD could indicate that this subgroup is a different entity. HLA‐DRB1*13:01 may represent a specific risk factor for inflammatory bile duct disease.